From policy disaster to ecoocreativity as a political potential - MONTES MONTOYA, Angélica; BUSSO, Hugo (Utopía y Praxis Latinoamericana, 2024)
The perspective of ecoocreativity (a neologism that unites ecology, cooperativism and creativity) is to bring about a deliberate political abandonment of the economistic regulatory criteria of Saxon origin, instituted by New Public Management and the guidelines of the Washington Consensus. This is the cause of the current political disaster and the politics of disaster in Latin America. It is a necessary condition, on the one hand, to encourage social experience to propitiate the creation of a new ecological (eco-creative) class, which could establish the parameters of a new post-neoliberal imaginary. On the other hand, because it is necessary to avoid the repetition of the "more of the same" of hegemonic economism. Another alternative is the "eco-fascist" perspectives, the result of substantive democratic degradation. For this reason, we propose twelve criteria for action as a horizon of what is possible to experience collectively, to make a general contribution to the democratic political debate.